Different Light Sources and Physical Quantities to Be Monitored in Gas Sensing with Lasers - Cao, Qiuyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
This article first presents some background and facts about the development of the field of gas sensing with lasers. Subsequently, the relevant content about using lasers for gas sensing was introduced. The introduction starts with the technical system and laser light sources. Laser light sources include several important and widely used lasers. The research directions and content suitable were identified for different lasers based on the existing research progress of different light sources. Starting from the Beer-Lambert law, the derivation process of gas concentration has been restored. Physical quantities detected in application have been classified and introduced, including absorption intensity, absorption line shape, Raman scattering intensity, photoacoustic signal and transmittance, and several physical quantities which are with high relevance to the previous text were derived. At the end of the article, the author summarized the article and provided an outlook on future development of gas sensing with lasers.